دراسات معجمية ولغوية تقابلية للدارسين في الجامعات الماليزية = Dirasat mu'jamiyah wa lughawiyah taqabuliyah lil-darisin fi al-jami'at al-Maliziyah. 2nd. ed - Dollah, Nafi@Hanafi; Abdullah, Nur Azlina (IIUM Press, 2016)
This book presents a study on Arabic lexicography and lexicology, and traces the fundamentals of these two sciences which have the importance in manifestation of its use from its classical resources, also traces the theories of modern linguistics which have to do with methodology of dictionaries. As it deals with the Arabic Malay bilingual dictionaries, it studies on word structure and meaning in Malay Language and how does it meet the word structure and meaning in Arabic language from the perspective of analytical contrastive study. It tries to highlight the importance of linking the science of Arabic lexicography and lexicology with the learners in Malaysian universities, since the Arabic Malay bilingual dictionaries have contributed significantly to the development of civilization in the region throughout the centuries. Apart from that, this book attempts to give the Arabic learners among the non-Arabic speakers some guidance and advice, as well as refer them to the importance of dictionaries in scientific careers. In the absence of Arabic teachers or professors, dictionaries will take the role of the teacher who can dispel confusion and anxiety of students and give them convincing answer on the word meaning, use and condition. On the other hand, the book reviews the civilizational role of the ancient and modern dictionaries, and their importance in maintaining and preserving the purity of the Arabic language as well as its serenity, splendour and survival. This book also highlights the great contributions of the Arabic Malay lexicographers to the spread of the Arabic language in the Malay Archipelago. It would therefore not be too great an exaggeration to say that this book is encyclopedic in its field and environment which is worth reading it, as it may not dispense with any Malaysian learner wants to be guided to the old Arabic monolingual or bilingual dictionaries, as well as it could be one of the best reference for those who are involved in the field of translation